Soviet Legacy and Colonial Mentality: Continuity and Change in Ukraine’s Higher Education - Oleksiyenko, Anatoly (East/West, 2023)
This article considers the forces that impeded university reform in Ukraine prior to the Russian invasion in 2014 and the onset of the full-scale war in 2022. Ukraine’s post-Soviet educational system, which was originally designed to reproduce the subservience, compliance, and rigidity of the Russian and Soviet empires, preserved administrative mechanisms and entitlements that curbed institutional transformation. Russia’s invasion, however, spurred universities in Ukraine to make a radical move away from the Russian/Soviet template of higher education. This paper contextualizes the contentious history of Russo-Ukrainian relations within a discussion of the constraints spawned by the Soviet legacy and colonial mindset in Ukrainian universities. An analysis of the challenges to transformation is followed by policy recommendations for reformers and intellectual leaders seeking to decolonize their academic communities through the internationalization of higher education.